Review of the taxonomy and conservation status of the Ecuadorian Glassfrog Centrolenella puyoensis Flores & McDiarmid (Amphibia: Anura: Centrolenidae) - Cisneros-Heredia, Diego F.; Mcdiarmid, Roy W. (Zootaxa, 2006)
The Glassfrog Centrolenella puyoensis Flores & McDiarmid is a taxon known only from the female holotype, and recently placed in the genus Centrolene due to its supposed close relationship with Centrolene mariae (Duellman & Toft). Herein we report new material of puyoensis, including adult male specimens previously unknown. We propose the new combination Cochranella puyoensis (Flores & McDiarmid) n. comb., in recognition of the state of the humeral crista ventralis in males of this species, which lack a humeral spine. The hypothesis of relationships between three species, including puyoensis, proposed as the mariae species-group is questioned as it was based on phenetic rather than derived characters. We present new data that extend the distributional range of Cochranella puyoensis, and define its range along the Foothill Evergreen forests from 400 m to 1000 m above sea level in the provinces of Napo, Orellana, and Pastaza. New data presented herein also permit a re-evaluation of the conservation status of the species, previously classified under the IUCN category of Critically Endangered. We recommend that Cochranella puyoensis be reclassified as “Endangered”: EN B1ab(i,ii,iii)+2ab(i,ii,iii); based on a better understanding of the presence of the species, its occupancy area, number of known localities, and habitat quality status.